2017
DOI: 10.1186/s11671-017-1853-y
|View full text |Cite
|
Sign up to set email alerts
|

Size, Stability, and Porosity of Mesoporous Nanoparticles Characterized with Light Scattering

Abstract: Silicon-based mesoporous nanoparticles have been extensively studied to meet the challenges in the drug delivery. Functionality of these nanoparticles depends on their properties which are often changing as a function of particle size and surrounding medium. Widely used characterization methods, dynamic light scattering (DLS), and transmission electron microscope (TEM) have both their weaknesses. We hypothesize that conventional light scattering (LS) methods can be used for a rigorous characterization of mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(95 citation statements)
references
References 44 publications
6
88
0
1
Order By: Relevance
“…The word porosity is also used as a generic term, implicitly incorporating other related characteristics such as pore morphology (e.g. pore volume, pore size) or specific surface area [3][4][5][6]. Porosity has a profound impact on particle chemistry, due to the facts that i) it can make the particles permeable, and ii) an increase in specific surface area boosts the activity of the surface and the adsorption of molecular species [7,8], thereby promoting various industrial and environmental science applications [5].…”
Section: Numerousmentioning
confidence: 99%
“…The word porosity is also used as a generic term, implicitly incorporating other related characteristics such as pore morphology (e.g. pore volume, pore size) or specific surface area [3][4][5][6]. Porosity has a profound impact on particle chemistry, due to the facts that i) it can make the particles permeable, and ii) an increase in specific surface area boosts the activity of the surface and the adsorption of molecular species [7,8], thereby promoting various industrial and environmental science applications [5].…”
Section: Numerousmentioning
confidence: 99%
“…Among all types of nanoparticles studied worldwide, mesoporous silica and polymeric nanoparticles are the two that have been investigated more. Mesoporous silica nanoparticles (MSNs), have a high surface area, unvarying porosity, stable aqueous dispersion, and in vivo biodegradability [27]. In the last five years, the number of published data describing the use of MSN has increased significantly, especially for biomedical applications, where precise control over particle size, shape, pore size, and pore geometry is highly appreciated [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Skoda et al, this type of synthesis allows a good reaction control on an atomic scale and the formation of homogeneous dispersions . DLS measurements (Figure ) showed that nanoparticles with 5 nm of effective diameter, 0.197 of polydispersity, proper distribution, and correlation function were obtained . Sol‐gel processing parameters (such as pH, water/alkoxides ratio, temperature, and time) can control the size and morphology of the nanoparticles as well as the degree of homogeneity of the multicomponent inorganic materials.…”
Section: Resultsmentioning
confidence: 58%